Efforts to Improve Understanding of Immunization During the Time of The Covid-19 In Tamiang Village, Tangerang Regency - Fara Fitriyani; Denisa Athaullah Mina; Jiyad Ghani Priatna; Anastasia Cindhy Dhamyani; Baggi Cahaya Restu Imron; Brianita Susansyadza Anindyasara; Devalia Elisabeth; Felixia Kristi Simbolon; Imam Arrazy Nasution; Galih Aji Pramono; Muhammad Syahrul Ramadhan; Sonya Mutiara Sarah Runtu (MOVE: Journal of Community Service and Engagement, 2022)
Immunization is an action that is actively carried out to increase immunity against disease in a person so that if the person is exposed to the disease only mild symptoms are experienced. Immunization aims to provide protection to a person against disease through the provision of vaccines. Immunizations that must be given according to the Indonesian government and WHO include; Immunization for Polio, Measles, Hepatitis, DPT, and BCG. The purpose of this community service is to increase public understanding about immunizations which must still be given in full during the Covid-19 pandemic. The community service method used is to provide health education in the form of counseling to the community in Tamiang Village. Data obtained through the evaluation of the instrument related questions about the importance of immunization. The community service team in collaboration with health workers from the Gunung Kaler District Health Center provided material on the importance of complete immunization during the Covid-19 pandemic. From the results of the pre-test 74,31% and post-test 88,89%, it was concluded that there was an increase in public knowledge about the importance of immunization. Knowledge is an important domain and is a factor that determines a person's initial behavior. it was concluded that there was an increase in public knowledge about the importance of immunization. Knowledge is an important domain and is a factor that determines a person's initial behavior. it was concluded that there was an increase in public knowledge about the importance of immunization. Knowledge is an important domain and is a factor that determines a person's initial behavior.